2023
DOI: 10.3390/jcdd10050218
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Sports Practice and Atrial Fibrillation: An Updated Review of a Complex Relationship

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia in clinical practice, and it is an enormous burden worldwide because of its high morbidity, disability and mortality. It is generally acknowledged that physical activity (PA) is strongly associated with a significant reduction in the risk of cardiovascular (CV) disease and all-cause mortality. Moreover, it has been observed that moderate and regular physical activity has the potential to reduce the risk of AF, in addition to improving overall wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
(144 reference statements)
1
4
0
Order By: Relevance
“…Moreover, similar findings were demonstrated by Aizer et al in their research on humans [46]. Petrungaro et al indicate that the mechanism of AF in elite athletes is still largely speculative [47]. A large number of studies have shown the higher frequency of this arrhythmia, for example, in marathon runners [46], runners exercising 7 days per week, and long-term competitive swimmers [48].…”
Section: Physical Activitysupporting
confidence: 65%
“…Moreover, similar findings were demonstrated by Aizer et al in their research on humans [46]. Petrungaro et al indicate that the mechanism of AF in elite athletes is still largely speculative [47]. A large number of studies have shown the higher frequency of this arrhythmia, for example, in marathon runners [46], runners exercising 7 days per week, and long-term competitive swimmers [48].…”
Section: Physical Activitysupporting
confidence: 65%
“…Studies have observed that the prevalence of AF in athletes is 2–10 times greater than that in the general population ( Sharma, 2018 ). This finding suggests a U-shaped relationship between sports and AF ( Aizer et al, 2009 ; Andersen et al, 2013 ; La Gerche and Schmied, 2013 ; Morseth et al, 2016 ; Sciarra et al, 2022 ; Petrungaro et al, 2023 ), whereby AF seems to increase due to either deficient or excessive sports practice, and patients instead benefit from moderate exercise. The assumed mechanisms underlying this observation include fibrosis or inflammation, hemodynamic variations leading to left atrial enlargement, vagal tone, and genetic factors triggered by physical exercise ( Flannery et al, 2017 ).…”
Section: Prevalence Of Af In Athletesmentioning
confidence: 95%
“… 5 10 Vigorous exercise has been linked to a higher incidence of AF in veteran male, but not female, endurance athletes, 11 though some studies have found a reduced risk of AF in non-elite moderate physically active men. 12 Additionally, some large population studies have suggested moderate or even vigorous physical activity may reduce the risk of AF in physically active females. 13 14 However, this sex-specific difference in elite endurance athletes has been questioned due to very few studies on female athletes.…”
Section: Introductionmentioning
confidence: 99%